2023
DOI: 10.1101/2023.08.20.554035
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

ATP Mediates Phase Separation of Disordered Basic Proteins by Bridging Intermolecular Interaction Networks

Divya Kota,
Ramesh Prasad,
Huan-Xiang Zhou

Abstract: ATP is an abundant molecule with crucial cellular roles as the energy currency and a building block of nucleic acids and for protein phosphorylation. Here we show that ATP mediates the phase separation of basic intrinsically disordered proteins (bIDPs). In the resulting condensates, ATP is highly concentrated (apparent partition coefficients at 200-5000) and serves as bridges between bIDP chains. These liquid-like droplets have some of the lowest interfacial tension (~25 pN/μm) but high zero-shear viscosities … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(15 citation statements)
references
References 43 publications
0
15
0
Order By: Relevance
“…Thus, the viscocapillary model seems to be a reasonable choice for estimating the surface tension of condensates formed by fully disordered proteins but not necessarily for those involving folded domains. However, given that the spatiotemporal evolution of condensates is only beginning to be explored, we advise caution in inferring the surface tension of condensates through indirect measurements via the viscocapillary model, particularly when environmental variables such as salt and ATP 99 play a role in regulating the thermodynamics and dynamics of biomolecular condensates.…”
Section: Methodsmentioning
confidence: 99%
“…Thus, the viscocapillary model seems to be a reasonable choice for estimating the surface tension of condensates formed by fully disordered proteins but not necessarily for those involving folded domains. However, given that the spatiotemporal evolution of condensates is only beginning to be explored, we advise caution in inferring the surface tension of condensates through indirect measurements via the viscocapillary model, particularly when environmental variables such as salt and ATP 99 play a role in regulating the thermodynamics and dynamics of biomolecular condensates.…”
Section: Methodsmentioning
confidence: 99%
“…In addition to charge neutralization, we suspected that ions could also fortify intermolecular interactions by bridging between proteins, similar to the role played by ATP molecules in driving phase separation of positively charged IDPs. 28 Indeed, we found that Clhas a tendency to bind with Arg and other sidechains from multiple chains and likewise, Na + has a tendency to bind with backbone carbonyls and sidechain oxygens from multiple chains (Figure 4A).…”
Section: Ions Act As Bridges Between Protein Chains To Drive Condensa...mentioning
confidence: 85%
“…2 For example, these simulations showed that ATP, a small molecule with a -4 charge, bridges between positively charged IDP chains in driving phase separation. 28 The intermolecular interactions quickly break and reform, explaining why the condensates can rapidly fuse despite very high macroscopic viscosity. Similarly, quick breakup and reformation of salt bridges in a heterotypic condensate allow the protein molecules to be extremely dynamic in a highly viscous environment.…”
Section: Introductionmentioning
confidence: 99%
“…They observed slab formation in the simulations. Kota et al 135 used SpiDecbased all-atom simulations to characterize the condensate formed by mixing a small basic IDP (bIDP) called protamine with ATP. In neither of these last two studies the solute molecules in the dense slab exchanged with the dilute phase in the available simulation time.…”
Section: Levels Of Representation Of Biomolecular Systems In Simulationsmentioning
confidence: 99%